Dopaminergic Vulnerability in Parkinson Disease: The Cost of Humans' Habitual Performance. Issue 6 (June 2019) - Hernandez, Ledia F.; Obeso, Ignacio; Costa, Rui M.; Redgrave, Peter; Obeso, Jose A.
Abstract : Humans can simultaneously combine automatic/habitual and voluntary/goal-directed aspects of behavioral control. Habitual routines permit us to perform well practiced task-components with minimal or no voluntary attention. Evidence from animal and human investigations indicates that dopaminergic neurons in lateral substantia nigra, which innervate the sensorimotor striatum, are engaged during the acquisition and performance of automatized skills and habits. Typically, in Parkinson disease (PD), there is a differential loss of dopamine, which occurs earliest and most severely in the caudal sensorimotor striatum, a subdivision of the striatum implicated in habitual control. We suggest that frequent reliance on habitual performance may be a critical functional stressor, which, when combined with other more general risk factors, could explain the selective neurodegeneration of the nigrostriatal motor projection in PD. Highlights: Goal-directed and habitual functions are displayed in distinct striatal territories. The habitual system engages and depends upon the dopaminergic projection from the lateral SNpc tier to the caudal striatum. The onset of the classic motor signs of PD is associated with fairly selective degeneration of the nigrostriatal projection mediating automatic habitual activity. Bradykinesia/akinesia, a cardinal feature of PD, is directly associated with disruption of the habitual system/motor circuit. Focal motor onset implies specific vulnerability of the dopaminergic sensorimotor nigrostriatal projection. Accordingly, we propose that frequent reliance on habitual performance may represent an additional, potentially toxic functional stressor, which could explain the somatotopic onset of PD cardinal features and the differential patterns of neurodegeneration within the nigrostriatal dopamine system. Who eventually develops PD would depend upon interaction between the proposed functional vulnerability and associated general risk factors such as genetics, environmental influences, and comorbidities.